The Prevalence of Swarming Genes in Escherichia coli Isolated from UTI and Catheter-Associated UTI - Kaittan, Hamza I.; Flayyih, May T. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Urinary tract infections are one of the most common bacterial illnesses among the public and in hospital settings. A prevalent nosocomial disease is catheter-associated urinary tract infection (CAUTI). The risk of infection increases with urinary catheterization, making it easier for Escherichia coli to colonize the urinary system. Uropathogenic E. coli (UPEC) specifically adapts to survive in challenging urinary tract conditions. Treating CAUTI accurately and effectively can be difficult. An important health concern nowadays is drug-resistant bacteria.Objectives: To assess the prevalence of swarming genes in E. coli responsible for UTIs and catheter-associated UTIs, and determine their antibiotic resistance.Methods: A total of 143 clinical specimens of urine and catheter samples were collected from two teaching hospitals in Baghdad city between October and December 2023. The bacteria were identified, and their antimicrobial susceptibility was tested. Conventional PCR methods were used to determine the bacteria and detect swarming genes (flhC, flhD, and recA).Result: Out of 143 samples, 44 isolates were identified as E. coli (35 isolates from UTIs and 9 isolates from catheters). These isolates exhibited varying sensitivities to antibiotics, most being multi-drug resistant (MDR). They were highly resistant to tetracycline (72.7%) and highly susceptible to imipenem (93.2%). Among these isolates, 16 were identified (12 from UTIs and 4 from catheters). All the highly swarming and multidrug-resistant E. coli isolates were found to possess the three tested swarming genes (flhC, flhD, and recA), as determined by conventional PCR.Conclusion: Escherichia coli is more prevalent in UTIs than in catheters. The number of isolates demonstrating the ability to swarm was found to be higher in UTIs, and these isolates also exhibited the capability to swim. Most E. coli isolates are multidrug-resistant and can swarm.